Cabbage Leaf Compress (Brassica oleracea): A Natural Remedy for Reducing Breast Engorgement Pain in Postpartum - Dewi, Mariza Mustika; Kurniawati, Erna Yovi; Rochkmana, Meika Jaya (Medico Insight Innovation Initiative, 2024)
Breast engorgement occurs in 1 out of 8000 cases, with research reporting prevalence rates between 20-70%, while in Indonesia it reaches 37%. This condition can lead to discomfort for the mother, including symptoms like pain, breast hardness, difficulties for the baby to latch, mastitis, abscesses, and potential breastfeeding failure. Cabbage (Brassica Oleracea Var. Capitata) has been shown to alleviate breast swelling due to its sulphate content, which helps dilate capillary blood vessels, improve blood circulation, and promote the reabsorption of fluid trapped in the breast tissue. A quasi-experimental one-group pretest-posttest design was employed, involving 32 participants. Statistical analysis was conducted using the Wilcoxon test. The results revealed that, prior to treatment, most respondents (65.6%) experienced moderate pain, while 34.3% reported severe pain due to breast engorgement. Post-treatment, 75% of respondents experienced moderate pain, followed by 21.8% with mild pain, and only 3.1% reported severe pain. The Wilcoxon test indicated a p-value < α (0.05), suggesting a significant effect of cabbage leaf compresses on reducing breast pain in postpartum mothers. In conclusion, cabbage leaf compresses effectively reduce breast engorgement pain in postpartum mothers.